2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00220
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Supervised Skin Detection by Network With Mutual Guidance

Abstract: In this paper we present a new data-driven method for robust skin detection from a single human portrait image. Unlike previous methods, we incorporate human body as a weak semantic guidance into this task, considering acquiring large-scale of human labeled skin data is commonly expensive and time-consuming. To be specific, we propose a dual-task neural network for joint detection of skin and body via a semi-supervised learning strategy. The dualtask network contains a shared encoder but two decoders for skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…According to the analysis of the experimental results, the performance rates of the proposed scheme are 95.40%, 92.33%, and 4.60% for the true positive rate, accuracy, and false negative rate, respectively. In recent years, many studies have reported of high performance in the harmful content detections using various deep learning approaches [6][7][8][9][10][11]13,14]. Among the studies, some use video frame image or video clips [7][8][9][10][11], motion analysis [6], or age prediction from facial images [14] as the visual element of input content to determine the harmfulness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the analysis of the experimental results, the performance rates of the proposed scheme are 95.40%, 92.33%, and 4.60% for the true positive rate, accuracy, and false negative rate, respectively. In recent years, many studies have reported of high performance in the harmful content detections using various deep learning approaches [6][7][8][9][10][11]13,14]. Among the studies, some use video frame image or video clips [7][8][9][10][11], motion analysis [6], or age prediction from facial images [14] as the visual element of input content to determine the harmfulness.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the performance results of these approaches, the approach of [6] with the accuracy rate of 95.1% and the approach of [7] with the true positive rates of 97.52% are showed better performance than the enhanced multimodal stacking scheme suggested in this study. However, since the techniques used in [6][7][8][9][10][11]13,14] cannot properly detect the harmful contents based on the acoustic elements, the proposed scheme in this paper, which includes an auditory element detection, can be evaluated as more advanced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Content may change prior to final publication. ject detection [55], and skin detection in a single human portrait image [56]. Domain adaptation is a learning task that enables an inference model on a source domain to perform on a target domain, when the data distributions between the two domains are different.…”
Section: Semi-supervised Domain Adaptationmentioning
confidence: 99%